KAJIAN POSISI TAWAR UD. MANDIRI ROTAN DALAM STRUKTUR PASAR INDUSTRI ROTAN (Calamus spp) DI WILAYAH KABUPATEN BANJAR DAN KOTA BANJARBARU PROVINSI KALIMANTAN SELATAN - Susilawati Susilawati (Universitas Lambung Mangkurat, 2014)
This study aims to determine the type of market structure that existed at the company rattan industry in the Banjar district and Banjarbaru City; knowing bargaining UD. Mandiri Rotan cane industry in the market structure in the Banjar district and Banjarbaru City; and how the strategy UD. Mandiri Rotan in Rattan industry market structure in the Banjar district and Banjarbaru City. The results of this study can be considered in the selection of rattan industry marketing strategies in the Banjar district and Banjarbaru City, can provide an overview and information for local governments within the framework of fostering marketing rattan industry in the Banjar district of Banjarbaru City as well and can enrich science for society in general and students of the Faculty of Forestry in particular. Market structure of the rattan industry in the Banjar district and Banjarbaru city is oligopoly, since only 4 (four) firms rattan industry is still operating both in the Banjar district and Banjarbaru City. 4 (four) rattan industry are PT. Sarikaya Sega Utama, UD. Mandiri Rotan, UD. Rotan Sega Mas and UD. Ihsan. Bargaining position UD. Mandiri Rotan cane industry in the market structure in the Banjar district and Banjarbaru City is oligopoly. Relative Market share date UD. Mandiri Rotan for 5 (five) years, ranging between 38.46% - 39.73%. The strategy can be applied by UD. Mandiri Rotan is currently developing a product strategy, distribution strategy and the strategy of quality goods.